Sialolith: assessment of 3 cases with clinical, radiographic and ultrasonographic findings - Melih Özdede; Nur Hacıosmanoğlu; Elif Kaya; Halil Özer; Emre Akın; Anıl Seçkin; Sharif Rzayev (Gazi University, 2016)
INTRODUCTION: Sialoliths (salivary gland stones) are calcified obstructions that occur in the salivary gland or duct. Sialolith is the most common disease of the salivary glands. Majority of the sialoliths occur in the submandibular gland and can be observed at almost any age. For the diagnosis of sialolith, conventional radiography, ultrasonography and computed-tomography can be used together with clinical examination. CASE REPORT: In the first case, radiopacities were seen under the right mandibular corpus and in the left mandibular angulus region on panoramic radiographs of a 66-year-old female patient. Ultrasonographic evaluation showed these radiopacities to be sialoliths. The patient had no other symptom and was, therefore, followed periodically. The second case was a 61-year-old male patient; in the intraoral examination, hard masses were detected in the left submandibular gland region and no salivary flow was observed in the left Wharton duct. Radiopacities were seen on panoramic and mandibular occlusal radiographs. On ultrasonography, these appeared to be sialoliths and were removed intraorally by excision. The third case was a 55-year-old female patient applied to our clinic with pain on the right cheek and ear while eating. In the intraoral examination, inflammation was detected in the right Stenon duct. On ultrasonography, sialolith and infected parotid gland with heterogeneous echogenicity were noticed. The sialolith was removed surgically under general anesthesia. CONCLUSION: Application of appropriate imaging techniques is important for the diagnosis of sialolith. The diagnosis and treatment of sialolith requires multidisciplinary clinical approach.